The crisis of liberal democracy and the return of fascism - Velásquez Insignares, Andrés Eduardo (2025)
The fall of Soviet communism consolidated liberal democracy and the market economy as the dominant model for social organization in the 21st century. However, over time, fascism has resurfaced with force, and its advance has become particularly evident in the context of the current government of the United States. This article aims to explore the causes behind the return of this phenomenon, focusing specifically on the American case. The author’s critical analysis addresses the relationship between fascism and post-truth politics, the emergence of spaces for white supremacy and attacks on women and minorities, key factors behind the Republican return to power after their 2020 defeat, and reflections on whom the political model in the Global North truly serves. Based on this inquiry, the article proposes alternatives for strengthening democracy.